EFFECT OF QUALITY OF SERVICE ON CUSTOMER SATISFACTION ON GALAXY MART MANADO - FANDA OLIVIA BEATRICE SEGE; Tinneke M. Tumbel; Olivia Walangitan (Universitas Sam Ratulangi, 2017)
Retail business spread across the country is experiencing rapid development. Thisdevelopment is due to retail customers who prefer to buy different items in one place. Of themany marketing activities, supermarkets, mini markets and department stores compete to offera variety of shopping facilities ranging from services provided, discounts, payment options,and other facilities to create a sense of satisfaction for customers in shopping. The mainproblem in this research is